Innovative governance systems and green innovations of agriculture-related enterprises based on the approach of fuzzy-set qualitative comparative analysis - Bao, Huricha; Chen, Chibo; Liu, Yuemin (Frontiers in Environmental Science, 2022)
The Green Innovation (GI) of agriculture-related enterprises has been an important factor to the ecological and sustainable development of agriculture. This research integrates the eight elements of the internally and externally governing mechanisms in the Innovative Governance System (IGS), adopts The fuzzy-set qualitative comparative analysis （fsQCA）from the configuration perspective, taking the data of A-shares' listed agricultural companies in Shanghai and Shenzhen stock markets from 2007 to 2019 as samples, and exploring the configuration effects of highly green innovations(GIs) from the collaborative matching of various elements of the enterprises' IGS. The research results showed that:(1)A single element of this IGS was unable to become a requisite for agriculture-related enterprises to generate the highly GIs, but government subsidies played a more universal role in such process;(2)The "multiple synergies" of various elements in the enterprises' IGS formed 6 different configurations to drive highly GIs, namely 3 major models of internal and external supervisions with external incentive, internal supervision with internal and external incentives, internal and external supervisions with internal and external incentives;(3)There were 5 different paths for the IGS of agriculture-related enterprises to generate non-highly GIs, which were in asymmetry with the configuration paths to generate the highly GIs.